Menghadapi Persaingan Sengit Lembaga Pendidikan: Strategi Diferensiasi dalam Pemasaran Lembaga Pendidikan Islam di Indonesia - Muh Ibnu Sholeh (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
This study aims to provide an in-depth understanding of the differentiation strategy in marketing educational institutions. Through research and analysis, this study will explore practical concepts, theories and strategies that can be applied by educational institutions to differentiate themselves and overcome fierce competition in the world of education so that they can compete and provide significant competitive advantages. The method used in this research is library research method. Library-based research is a form of research that uses literary works as the object of study. Researchers study the literature, writings and sources that are closely related to the problem under study. Collecting data by looking for sources from various sources such as books, journals, and existing research. The data obtained from the literature study were analyzed using an interactive qualitative model. This data analysis model consists of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the application of a differentiation strategy in the marketing of educational institutions has a positive impact on attracting students' interest. By implementing a Differentiation Strategy in Educational Institution Marketing such as developing a strong image and identity, Focusing on specific market segments and understanding their needs, Innovation in educational programs and curriculum, Quality student services and experiences, Use of technology in learning and Collaboration with industry and Such strategic partnerships can differentiate themselves from competitors and attract the attention of prospective students and will provide a significant competitive advantage.